2005
DOI: 10.1080/00288233.2005.9513627
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of soil fluorine: Its impact on the fluorine metabolism of dairy cows

Abstract: In grazing cattle high fluoride (F) intakes are associated with soil ingestion. The ingestion of soil (F) (93% of dietary F) at a rate of 1562 mg F day-1 by mature dairy cows over 63 days, when compared with animals on basal diet (no soil) providing 110 mg F day-1 , resulted in an increase in mean serum F concentrations from 0.10 to 0.22 mg litre -1 , and no detectable change in mean metacarpal F concentrations (1125 mg F kg -1 DM), while the apparent absorption of soil F was 44%. However, an intake of soil F … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…permanent dairy pastures). However, Grace et al (2005) could fi nd no effect of soil F ingestion on serum or bone concentrations of F in dairy cows.…”
Section: Fluorinementioning
confidence: 88%
“…permanent dairy pastures). However, Grace et al (2005) could fi nd no effect of soil F ingestion on serum or bone concentrations of F in dairy cows.…”
Section: Fluorinementioning
confidence: 88%
“…The same study further revealed that the total daily intake of metals by sheep can be as high as 1685 mg, 486 mg and 60 mg for lead (Pb), zinc (Zn) and copper (Cu), respectively. Another earlier study by [9] showed that grazing young sheep ingest soil F at moderate to high rates; in fact, an order of 69-184 mg F/day, for 63 days, was observed. These findings confirm the potential of soils in supplying F to animals.…”
Section: Introductionmentioning
confidence: 87%
“…In the absence of industrial output and agricultural contamination, animals are typically introduced to excess fluoride via long-term (i.e., monthly or multi-annual; Grace et al, 2005) ingestion of geothermal waters and by foraging in enriched areas, such as those composed of volcanic soils (Shupe et al, 1984. Prehistoric bison regularly inhabiting and utilizing such environments, either continually or through the course of migration, may have invited toxicosis.…”
Section: Fluoride Toxicosismentioning
confidence: 99%